Diez años de investigación en didáctica de las ciencias: realizaciones y perspectivas - Gil Pérez, D. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
This paper summarizes the research in science education undertaken by the international community during the past decade, paying a special attention to the Spanish production. We intend to show that science education has improved considerably during this period, becoming a coherent body of knowledge, and we present what could be, in our opinion, the main trends for the next future.